Analysis of Purchasing Decisions Based on Beauty Influencer Tasya Farasya, Electronic Word of Mouth (E-WOM), and Brand Image on Consumers of Skintific 5x Ceramide Barrier Moisturizer Gel Skincare Product in Surabaya - Nadilla Putri Pertiwi; Jojok Dwiridotjahjono (Universitas KH. Abdul Chalim Mojokerto, 2025)
The purpose of this study was to analyze the influence of beauty influencer Tasya Farasya, Electronic Word of Mouth (E-WOM), and Brand Image on Purchasing Decisions for Skintific 5x Ceramide Barrier Moisturizer Gel products in Surabaya. The development of the care and beauty industry is currently growing rapidly and is followed by a digitalization strategy in marketing a product. In the digital era, the role of beauty influencers is consideres increasingly significant in shaping consumer perceptios, while E-WOM is an important factor in disseminating information about a product. In addition, a good brand image helps increase consumer trust and can encourage purchasing decisions. The type of research used in this study is associative research with quantitative methods. The sampling technique in this study is nonprobability samoling with a purposive sampling method. The data in this studi uses primary and secondary data. Primary data is obtained from questionnaires filled out by 100 respondents, while secondary data is based od sources relevant to the research topic. The results of this study based on the data analysis that has been carried out indicate that the existence of beauty influencer Tasya Farasya has a significant effect on purchasing decisions, E-WOM has a significant effect on purchasing decisions, and brand image also has a significant effect on purchasing decisions. In addition, these three factors simultaneously have a significant effect on the purchasing decision of Skintific 5x Ceramide Barrier Moisturizer Gel products in Surabaya. Therefore, this study confirms the importance of the role of beauty influencers, E-WOM, and brand image in implementing product marketing strategies. Abadi, T. W., & Hawa, E. F. (2024). Pengaruh E-WOM, Citra Merek, E-Commerce, dan Beauty Vlogger terhadap Keputusan Pembelian. Jurnal Ilmu Komunikasi, 21(1), 19–38. https://doi.org/10.24002/jik.v21i1.6406 Alfiana, D., Haris, A., & Im, N. ’. (2023). Pengaruh Kredibilitas Beauty Influencer dan Eelectronic Word Of Mouth (e-WOM) Terhadap Keputusan Pembelian Produk Bybdka (Studi pada Konsumen Bybdka di Jepara). Jebisku: Jurnal Ekonomi Dan Bisnis Islam IAIN Kudus, 1(1), 35–47. http://jim.ac.id/index.php/jebisku/ Ani, J., Lumanauw, B., & Tampenawas, J. L. A. (2021). Pengaruh Citra Merek, Promosi dan Kualitas Layanan Terhadap Keputusan Pembelian Konsumen Pada E-Commerce Tokopedia di Kota Manado. Jurnal Emba, 9(2), 663–674. Annisawati, A. A., & Suarsa, S. H. (2023). Pengaruh Elektronik Word of Mouth (E-WOM) and Brand Image Terhadap Keputusan Pembelian Konsumen Milenial di Bandung Pada era Pandemic Covid - 19. Jurnal Sekretaris & Administrasi Bisnis (JSAB), 7(1), 9–21. https://doi.org/10.31104/jsab.v7i1.247 Az-Zahra, P., & Sukmalengkawati, A. (2022). Pengaruh Digital Marketing Terhadap Minat Beli Konsumen. Jurnal Ilmiah (Manajemen, Ekonomi, Dan Akuntansi), 6(3), 2008–2018. Devi Pratiwi, Novi Sri Wiarti, Fitrianingsih, & Bobby Hartanto. (2024). Pengaruh Influencer Review, Brand Love, dan E-Wom Terhadap Keputusan Pembelian Produk Kosmetik Implora Melalui Kualitas Produk Sebagai Variabel Intervening pada Followers Instagram Imploracosmetics. Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 6(8), 6033–6049. https://doi.org/10.47467/alkharaj.v6i8.4365 Fadhilla, L. (2024). Analisis Media Monitoring terhadap Produk Baru Brand Skintific pada Bulan Maret 2024. Jurnal Bisnis Dan Komunikasi Digital, 1(3), 1–10. https://doi.org/10.47134/jbkd.v1i3.2754 Jannah, M., Kambolong, M., Ningtyas, C. P., Studi, P., Bisnis, A., Niversitas, U., & Oleo, H. (2023). Pengaruh Beauty Influencer Tasya Farasya Terhadap Keputusan Pembelian Produk Kosmetik PT. Paragon Technology Innovation (Studi Mahasiswa Jurusan Administrasi Bisnis). Business UHO: Jurnal Administrasi Bisnis, 8(2), 431–442. Kumbara, V. B. (2021). Determinasi Nilai Pelanggan dan Keputusan Pembelian: Analisis Kualitas Produk, Desain Produk, dan Endorse. Jurnal Ilmu Manajemen Terapan, 2(5), 604–630. Marcelia, L., Rizqyana, L., & Hermansyah, N. A. (2024). Pengaruh Digital WOM Dan Personal Branding Influencer Tasya Farasya Terhadap Persepsi Produk Kosmetik Yang Berdampak Pada Keputusan Pembelian. Jurnal Strategi Bisnis Teknologi, 1(3), 104–120. https://doi.org/10.61132/jusbit.v1i3.265 Nurasmi, & Andriana, A. N. (2024). Pengaruh Peran Beauty Vlogger, Electronic Word of Mouth (E-WOM), dan Brand Image Terhadap Keputusan Pembelian Produk Skincare Skintific di Samarinda. Management Studies and Entrepreneurship Journal, 5(2), 4901–4920. http://journal.yrpipku.com/index.php/msej Pawestriningrum, W., & Roostika, R. (2022). The Effect of Beauty Influencer Trust on Brand Credibility, Advertising Credibility, Corporate Credibility and Purchase Intention of Local Skincare Products. Selekta Manajemen: Jurnal Mahasiswa Bisnis & Manajemen, 01(01), 65–80. https://journal.uii.ac.id/selma/index Pratama, I. W., & Ayesha, I. (2022). Digital Marketing (Tinjauan Konseptual) (R. Wujarso, Ed.; 1st ed.). PT. Global Eksekutif Teknologi. www.globaleksekutifteknologi.co.id Putri, J., Listyorini, S., & Budiatmo, A. (2023). Pengaruh Influencer Marketing dan Brand Image Terhadap Keputusan Pembelian (Studi Pada Konsumen Produk Pond’s di Kota Semarang). Jurnal Ilmu Administrasi Bisnis, 12(3), 922–933. Rohmawati, S. P., Ahmadi, M. A., & Surakarta, M. (2024). Analisis Pengaruh Influencer Marketing terhadap Brand Awareness dan Purchase Decision pada Produk The Originote. Jurnal Ekonomi Dan Manajemen, 2(1), 1003–1013. https://doi.org/10.62710/ys2tks33 Zukhrufani, A., & Zakiy, M. (2019). The Effect of Beauty Influencer, Lifestyle, Brand Image, and Halal Labelization Towards Halal Cosmetical Purchasing Decisions. Jurnal Ekonomi Dan Bisnis Islam, 5(2), 168–180.